PENDIDIKAN KESEHATAN PEMANFAATAN ASI EKSLUSIF DAN MAKANAN BERGIZI SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Atalia Pili Mangngi; Brigita Dina Manek; Nabilah Nurul Ilma (Pusat Riset dan Inovasi Nasional, 2022)
This community service aims to overcome the problem of malnutrition experienced by the community which is a complex problem that needs to be overcome. Because it has an impact on the incidence of stunting that occurs in children Breastfeeding is an important factor for the growth and development and health of children. Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to the provision of food that does not match nutritional needs. The problem of stunting in Indonesia is a serious threat that requires proper handling. Based on data from the Indonesian Toddler Nutrition Status Survey (SSGBI) in 2019, the prevalence of stunting in Indonesia reached 27.7%. According to the Ministry of Health of the Republic of Indonesia in 2018, several factors influence the problem of stunting in infants and toddlers, namely factors from the mother and poor parenting, especially the behavior and practice of feeding children which can cause children to become stunted if they do not provide adequate nutritional intake and good.